2001
DOI: 10.1177/088307380101601206
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Inflammatory Response in Subacute Sclerosing Panencephalitis (SSPE)

Abstract: The pattern of inflammatory infiltration was studied in the frontal brain biopsies of 28 cases with subacute sclerosing panencephalitis (SSPE) by immunohistochemistry. Lymphocytic infiltration and gliosis were common pathologic findings. CD4+ T lymphocytes were often observed in perivascular areas and CD8+ lymphocytes in the parenchyma. B lymphocytes were located in large perivascular cuffs associated with longer and slower disease. Major histocompatibility complex antigens, interferon-gamma, and tumor necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…36 Moreover, several previous studies have demonstrated that TNF-a was expressed in the brain of SSPE patients. 25,37,38 Our results suggest that the CSF levels of MMP-9 may indicate the degree of inflammatory damage associated with cytokines, especially TNFa, in SSPE. However, we could not determine a specific index indicating whether or not MMP-9 is produced in the CNS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…36 Moreover, several previous studies have demonstrated that TNF-a was expressed in the brain of SSPE patients. 25,37,38 Our results suggest that the CSF levels of MMP-9 may indicate the degree of inflammatory damage associated with cytokines, especially TNFa, in SSPE. However, we could not determine a specific index indicating whether or not MMP-9 is produced in the CNS.…”
Section: Discussionmentioning
confidence: 89%
“…In the brain of SSPE patients, CD4þ T lymphocytes, CD8þ T lymphocytes, and CD20þ B lymphocytes showed infiltration, especially in the perivascular regions. 25 These findings suggest that the immunocompetent cells in the blood invade the brain in SSPE patients. MMP-9 is a member of this family, which is capable of degrading collagen IV, a major component of the basement membrane of the cerebral endothelium and promotes the migration of cells through tissue or across the bloodebrainebarrier (BBB).…”
Section: Discussionmentioning
confidence: 97%
“…In the brain of SSPE patients, CD4+ T lymphocytes, CD8+ T lymphocytes, and CD20+ B lymphocytes were existed, especially in the perivascular regions [38]. These findings suggest that the immunocompetent cells in the blood invade the brain.…”
Section: Discussionmentioning
confidence: 95%
“…It is characterized by progressive cognitive deterioration followed by motor impairment, and usually leads to the death of the affected individual. Pathologically, brains of SSPE patients are described as "decorticated": Massive inflammation, glial activation, neuronal loss, and blood brain barrier breakdown typify this disease (2). Children are more likely to develop SSPE than adults following MV infection.…”
Section: Cns Infection and Diseasementioning
confidence: 99%